2014
DOI: 10.1007/s00394-014-0707-y
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy inhibitor 3-methyladenine potentiates apoptosis induced by dietary tocotrienols in breast cancer cells

Abstract: Introduction Tocomin® represents commercially available mixture of naturally occurring tocotrienols (T3s) and tocopherol (Ts) extracted from palm oil/palm fruits that possess powerful antioxidant, anticancer, neuro/cardioprotective and cholesterol lowering properties. Cellular autophagy represents a defense mechanism against oxidative stress and several anticancer compounds. Recently, we reported that tocotrienols induce apoptosis and endoplasmic reticulum stress in breast cancer cells. Methodology We studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 44 publications
1
26
0
1
Order By: Relevance
“…1a). These doses correspond to those previously reported for the antitumor activity of tocotrienols in cancer cell lines333435. Strikingly, the same treatment schedule did not affect the growth of human normal melanocytes at both time intervals (Fig.…”
Section: Resultssupporting
confidence: 89%
“…1a). These doses correspond to those previously reported for the antitumor activity of tocotrienols in cancer cell lines333435. Strikingly, the same treatment schedule did not affect the growth of human normal melanocytes at both time intervals (Fig.…”
Section: Resultssupporting
confidence: 89%
“…In addition, a previous study also found that hypoxia and endoplasmic reticulum stress induced by high glucose could activate autophagy as well [19] , which reminds us of the fact that high glucose is an important activator of cell autophagy. Du et al [9] found that 3-MA, which was proved to inhibit autophagy effec- tively [20,21] , could decrease total tube length, the number of branching points, and the average number of migrated cells (from 55 to 20/high-power field) in bovine aortic endothelial cells [9,10] . Our study had the same result showing that 3-MA reduced the number of capillary-like structures and migrated RF/6A cells promoted by high glucose.…”
Section: Discussionmentioning
confidence: 99%
“…3MA blocks autophagy through inhibiting class I and class III phosphatidylinositide-3-kinases (PI3K) [23, 24]. Class III PI3K is a lipid protein that phosphorylates the 3rd position on the inositol ring in phosphatidylinositol to form phosphatidylinositol-3-phosphate (PI3P), which is essential for the initial steps in autophagy [23].…”
Section: Introductionmentioning
confidence: 99%